Semantic and Phonemic Verbal Fluency in Parkinson’s Disease: Influence of Clinical and Demographic Variables - Ignacio Obeso; Enrique Casabona; Maria Luisa Bringas; Lázaro Álvarez; Marjan Jahanshahi (Behavioural Neurology)
Changes of cognitive function in PD have been extensively documented and defined as a ‘frontal’ type executive dysfunction. One of the main components of this executive dysfunction is the impairment of verbal fluency. The aim of the present study was to assess semantic and phonemic fluency in a large sample of PD patients and to investigate the effect of clinical and sociodemographic variables on verbal fluency in this patient group.